New Paradigms in Catalysis Inspired by Cytochromes P450 - Gao, Yanqun; Cheng, Lu; Shi, Wei; Ouyang, Yuejun; Han, Wei (Synlett, 2023)
Cytochromes P450 (P450s or CYPs) are versatile biocatalysts capable of realizing a broad range of synthetically challenging reactions. The development of synthetic catalysts/catalytic systems that model enzyme functions is a goal that has long been pursued. In this account, we mainly summarize our latest advances in the field of catalysis inspired by cytochromes P450, including reductive activation strategies for highly efficient oxidations and an unusual l-cystine-derived ligand as a model of P450s for highly efficient iron-catalyzed undirected arene C–H hydroxylation. These new paradigms highlight some of the catalytic properties of P450s, such as effective late-stage functionalization of complex targets, good reactive functional group tolerance, and high catalytic efficiency and selectivity.1 Introduction2 Reductive Activation Strategies for Oxygenation3 An Fe/Cysteine-Based Ligand as a Biomimetic Model of Cytochromes P450 for Arene C–H Hydroxylation4 Conclusion
Keywords: cytochromes P450; bio-inspired catalysis; iron catalysis; oxidation; late-stage functionalization; reductive activation strategy; I-cystine-derived ligand